Perbandingan Volume Overburden Menggunakan Metode Cut And Fill Dengan Truck Count pada Pit Raja PT. Rajawali Internusa Jobsite Muara Lawai PT. Budi Gema Gempita, Lahat Provinsi Sumatera Selatan - Muhammad Ilham Rasyidi; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2021)
PT. Rajawali Internusa is one of the companies engaged in the mining world as a unit of heavy equipment provider (contractor) from PT Budi Gema Gempita as the owner, located in Lahat, South Sumatra Province. in the mining process the survey method is used to determine the distance nad elevation as well as the height of the excavated area. In determining the volume of overburden stripping, survey activities are carried out and determining the ratio of the means of transportation. Result transportation means ritase in march 58,013 bcm and april 60,080 bcm, and the result measured by the survey in march were 57,105.45 bcm and in april 59,084.985 bcm resulting in losses of Rp. 13,613,250.00 and Rp 14,927,625.00 in march and april. The difference causes the calculation of the annual reserve to be inappropriate at 880,000 bcm. There is a greater difference in ritase volume due to the rolled back material, there are operators who are not performing well and the 12 bcm stipulated by the company has not yet been met